AMOSTRAGEM DE CIGARRINHAS (HEMIPTERA, CICADELLIDAE) ATRAVÉS DE ARMADILHAS DE MOERICKE EM CAFEEIRO ARÁBICA - Lara, R.i.r. (2022)
This study had for objective to evaluate the population fluctuations of the leafhoppers (Hemiptera, Cicadellidae) associated to Coffea arabica in Cravinhos, São Paulo, Brazil. The leafhoppers were sampled weekly by using 60 Moericke trap in the period of April/2005 to April/2006. Were collected 3.243 leafhoppers belonging to eight species: Bahita infuscata, Coelidiana diminuta, Dilobopterus costalimai, Docalidia bifurcata, Joruma (Joruma) sp., Labocurtidia sp., Oncometopia facialis and Scaphytopius irrorellus. The mostly frequency of the leafhoppers associated at coffee crop occurred in the rainy season; all the species of Cicadellidae collected were constants and the Moericke traps located at the median third of the plants were preferred for the capture of this group of insects. D. costalimai presented positive and significant correlations (p < 0.05) with the rainfall and maximum and minimum temperatures and O. fascialis was only with minimum temperature.